Beispiel Nr: 12
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(\frac{1}{3}/0)\qquad Q(1\frac{1}{3}/0) \\\\ \\ \textbf{Rechnung:} \\ P(\frac{1}{3}/0)\qquad Q(1\frac{1}{3}/0) \qquad a=1\frac{1}{3} \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=1\frac{1}{3}(x-\frac{1}{3})(x-1\frac{1}{3})\\ y=1\frac{1}{3}(x^2+x \cdot \left(-\frac{1}{3}\right) +\left(-1\frac{1}{3}\right)\cdot x +\left(-\frac{1}{3}\right)\cdot \left(-1\frac{1}{3}\right) )\\ y=1\frac{1}{3}(x^2 -1\frac{2}{3} x+\frac{4}{9}) \\ y= 1\frac{1}{3}x^2-2\frac{2}{9}x+\frac{16}{27} $